Influence of Treatment Package Time on outcomes in High-Risk Oral Cavity Carcinoma in patients receiving Adjuvant Radiation and Concurrent Systemic Therapy: A Multi-Institutional Oral Cavity Collaborative study. (March 2022) - I Ghanem, Ahmed; Woody, Neil M; Schymick, Mathew A; Joshi, Nikhil P; Geiger, Jessica L; Jillian Tsai, Chiaojung; Dunlap, Neal E; Liu, Howard Y; Burkey, Brian B; Lamarre, Eric D; Ku, Jamie A; Scharpf, Joseph; et al.
Highlights: Treatment package time encompasses number of days from surgery to end of radiation therapy. Longer treatment package time predicted worse survival for high-risk oral cavity cancer. Local and distant tumor recurrences were not influenced by treatment package time. All efforts are needed to expedite postoperative recovery and start treatment early. Concurrent chemotherapy did not compensate for prolongation of treatment package time. Abstract: Objectives: To explore the influence of treatment package time(TPT) in high-risk oral cavity squamous cell carcinoma(OCSCC) receiving adjuvant radiotherapy with concurrent chemotherapy(CRT). Materials and Methods: We queried our multi-institutional OCSCC collaborative database for cases diagnosed between 2005 and 2015 who underwent surgery followed by adjuvant CRT. All patients had high-risk features: extranodal extension(ENE) and/or positive surgical margin(PM). TPT was days between surgery to last radiotherapy fraction. Kaplan-Meier curves, log-rank p-values and multivariate analysis(MVA) were used to investigate the impact of TPT on overall(OS), disease-free(DFS), locoregional failure-free(LRFS) and distant metastases-free(DMFS) survival. Results: We identified 187 cases: median age 58 (range, 24–87 years), males 66%, and ever smokers 69%. ENE and PM were detected in 85% and 32%, and oral tongue and floor of the mouth constituted 49% and 18%, respectively. Median radiotherapy and cisplatin doses received were 66 Gy and 200 mg/m2. Overall, median TPT was 98 (range, 63–162 days). OS was worse for TPT > 90-days (n = 134) than TPT ≤ 90 (n = 53) at two-(65% vs. 71%) and five-years (45% vs. 62%); p = 0.05, with similar results for DFS. No influence on LRFS or DMFS was noted. More lymph nodes(LN) dissected( P = 0.039 ), T3-4 disease( P = 0.017 ), and unplanned reoperations( P = 0.037 ) occurred with TPT > 90-days. On MVA, TPT in 10-day increments was independently detrimental for OS (Hazard Ratio: 1.14; 95 %Confidence Interval [1–1.28]; P = 0.043 ), perineural invasion, age and positive LN ( p < 0.05 for all). Conclusion: In one of the largest multi-institutional cohorts, TPT > 90-days predicted worse OS for high-risk OCSCC receiving adjuvant CRT. All efforts are needed to optimize perioperative care and baseline conditions for favorable outcomes.